COMPARISON OF THE FLAP SURVIVAL WITH ISCHEMIC PRECONDITIONING ON DIFFERENT PEDICLES UNDER VARIED ISCHEMIC INTERVALS IN A RAT BILATERAL PEDICLED FLAP MODEL - Yildiz, KEMALETTİN; YILDIZ, KEMALETTİN; KARSIDAG, Semra; AKCAL, Arzu; YESILOGLU, Nebil; UGURLU, Kemal; OZAGARI, Aysim; Guneren, ETHEM; GÜNEREN, ETHEM; BAŞ, Lutfu (My University, 2014)
The study was undertaken to search whether pedicle selection for ischemic preconditioning (IP) and duration of global ischemia applied after IP influenced efficacy of IP on flap viability in epigastric adipocutaneous island flap with bilateral pedicles in rat model. In total, 159 rats were divided into one control and three (primary, secondary, or bilateral pedicle) IP treatment groups. IP was performed on different pedicles by three cycles of 10 minutes of pedicle clamping and 10 minutes of release. After IP procedure secondary pedicle was ligated in all groups, and flaps were exposed to 0, 1, 2, 4, or 6 hours of global ischemia by clamping primary pedicle. In control groups, after the perfusion of bipedicled flaps for 1 hour, left pedicle was ligated and flaps were exposed to global ischemia as in IP groups. On day 5 post-surgery, tissue samples and topographic measurements were taken. No significant differences in semi-quantitative scorings of polymorphonuclear leukocytes infiltration, chronic inflammation, interstitial edema, neovascularization, VEGF, and CD105 expression levels among groups were found (P > 0.05). Percentages of necrosis were consistently smaller in IP groups compared to controls for the same duration of global ischemia, with exception of the no-ischemia. Area of necrosis was significantly smaller in primary IP group versus secondary IP group in the absence of global ischemia (P 0.05). Thus, IP performed on different pedicles may ameliorate flap survival in a comparable fashion, depending on the duration of global ischemia. Secondary pedicle IP was as effective as primary pedicle IP and may be feasible in free flap transfers. (c) 2013 Wiley Periodicals, Inc. Microsurgery 34:129-135, 2014.